Inggris - Zain, Ine Alexsandrina Susiva; Sridadi, Ahmad Rizki (Jurnal Pijar, 2024)
This study aims to investigate aspects related to authentic leadership, its application in organizations, and the benefits and objectives associated with authentic leadership theory. Using a systematic literature review, the research examines 518 journal articles published in Scopus between 2013 and 2023. The data were drawn from 40 journals using RStudio and Bibliometrix applications, focusing on the 50 most globally cited articles. The findings show that authentic leadership is closely related to qualities such as honesty, transparency, and self-consistency. Additionally, the study provides a comprehensive historical analysis of the concept of authenticity and explains the fundamental principles and significant developments in Authentic Leadership (AL) theory. The RStudio and Bibliometrix methodologies, which have not been widely used in previous studies on authentic leadership, offer a new approach to this research. To enhance employee creativity, motivation, commitment, satisfaction, and performance, leaders are encouraged to adopt authentic leadership practices, which in turn can foster greater trust in their leadership abilities